ANALISIS PENGARUH HARGA, CITRA PERUSAHAAN, DAN KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN PENUMPANG SEBAGAI VARIABEL INTERVENING (STUDI PADA PENUMPANG AIR ASIA) - Aryadinata, Dhimas Angga; Idris, Idris (Diponegoro Journal of Management, 2020)
From previous research many who already examines antecedent of customer loyalty. Based on several research, there is still controversy about the result of one variable, service quality. The controversy about the result is within the effect of service quality on customer loyalty directly. Also supported with data from research object, Air Asia, which is had continuously decrease in total passengers annually until 2018. Hence, this research was conducted to discover the influence of service quality, added with price and corporate image to customer loyalty through customer satisfaction as an intervening variable on Air Asia passangers. Total samples used were up to 140 respondents who had used the services of Air Asia at least 2 times. This research utilized Structural Equation Modeling (SEM) for analysis technique and AMOS 22.0 for the analysis tool. The results of this study indicate that of the four hypotheses proposed, two of them are accepted, namely service quality have a positive and significant effect on customer satisfaction and customer satisfacion have a positive and significant effect on customer loyalty. Meanwhile, price and corporate image have negative and no significant effect on customer satisfaction.